The use of zones in teaching foreign languages - Lolayeva Gulniso Geldiyorovna (Zien Journals, 2022)
This article describes the basic principles and ways of teaching that serve to achieve the goals of reading and teaching foreign languages.
Keywords: Foreign Language Teaching; Storytelling; Playful Situation; Communicative Situations